FLAVONOIDS FROM SUDANESE ALBIZIA ZYGIA (LEGUMINOSAE, SUBFAMILY MIMO-SOIDEAE), A PLANT WITH ANTIMALARIAL POTENCY - Abdalla, Muna Ali; Laatsch, Hartmut (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Three flavonoids were isolated for the first time from the Sudanese medicinal plants Albizia zygia. Compounds 1-3 were identified by interpretation of ESI mass data, 1H, 13C and 2D NMR as well as by comparison with published data as 4’,7-dihydroxyflavanone (1) 3’,4’,7-trihydroxyflavone (2), 3-O-methylfisetin (3’,4’,7-trihydroxy-3-methoxyflavone, 3). All flavonoids were tested against Plasmodium falciparum, and only compound 2 showed high antimalarial activity (IC50 0.078 μg/ml).